The Adventist Schools: Development and Challenges - Furst, Lyndon G. (Catholic Education: A Journal of Inquiry and Practice, 2002)
The Seventh-day Adventist denomination operates schools and colleges around the globe. Beginning in 1853 with a small home school, the church’s systems includes over 4,500 elementary and 1,100 secondary schools, as well as 95 colleges and universities. This article briefly presents the development of this system and the philosophy that undergirds the education offered by the schools. Maintaining the unique identity of the Adventist schools is a special challenge for the future. Other challenges faced by the schools are briefly discussed.